2009
DOI: 10.1371/journal.pone.0004406
|View full text |Cite
|
Sign up to set email alerts
|

Poisoning Pyridoxal 5-Phosphate-Dependent Enzymes: A New Strategy to Target the Malaria Parasite Plasmodium falciparum

Abstract: The human malaria parasite Plasmodium falciparum is able to synthesize de novo pyridoxal 5-phosphate (PLP), a crucial cofactor, during erythrocytic schizogony. However, the parasite possesses additionally a pyridoxine/pyridoxal kinase (PdxK) to activate B6 vitamers salvaged from the host. We describe a strategy whereby synthetic pyridoxyl-amino acid adducts are channelled into the parasite. Trapped upon phosphorylation by the plasmodial PdxK, these compounds block PLP-dependent enzymes and thus impair the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 37 publications
0
46
1
1
Order By: Relevance
“…3b,c). At least one earlier study 29 has shown increased drug sensitivity as a result of targeted overexpression of a parasite protein (involved in vitamin B 6 metabolism), but this increased sensitivity was subtle when compared with that observed here. The increased oxythiamine sensitivity of 3D7-PfTPK þ parasites, together with our demonstration that oxythiamine is a substrate of PfTPK (Fig.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…3b,c). At least one earlier study 29 has shown increased drug sensitivity as a result of targeted overexpression of a parasite protein (involved in vitamin B 6 metabolism), but this increased sensitivity was subtle when compared with that observed here. The increased oxythiamine sensitivity of 3D7-PfTPK þ parasites, together with our demonstration that oxythiamine is a substrate of PfTPK (Fig.…”
Section: Discussioncontrasting
confidence: 72%
“…The GFP chimeras pARL-OxoDH-E1-GFP and IBA3-PDH E1a-GFP contain the first 100 amino acids of the N terminus of the respective protein fused to GFP. The constructs and the pARL1a vector (as mock plasmid) were transfected into P. falciparum and selected as described previously 29,48 .…”
Section: Methodsmentioning
confidence: 99%
“…Ellagic acid was dissolved in 0.3 M NaOH and equilibrated with 1× PBS to a final P. falciparum culture and antiplasmodial in vitro assay P. falciparum 3D7 were maintained in human erythrocytes at 37°C according to standard methods (Trager and Jensen 1976). The growth analysis was carried out according to Das Gupta et al (2005) and Müller et al (2009). Briefly, extracts and isolated compounds were tested against P. falciparuminfected erythrocytes in a [ 3 H] hypoxanthine incorporation assay.…”
Section: Extraction and Isolation Of Geraniin And Furosinmentioning
confidence: 99%
“…Transfection of malaria parasites was carried out as described previously. 62 Expression of GFP within the transgenic parasites was visualized in live cells using a Zeiss Axioskop 2 and the OpenLab software (Improvision). Parasite nuclei were stained with 0.2 μg ml − 1 Hoechst 33342 dye (Invitrogen).…”
Section: In Vivo Localization Of Gfp-tagged Pfaspatmentioning
confidence: 99%